2015
DOI: 10.1073/pnas.1410424112
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of folding energy landscape by charge–charge interactions: Linking experiments with computational modeling

Abstract: The kinetics of folding-unfolding of a structurally diverse set of four proteins optimized for thermodynamic stability by rational redesign of surface charge-charge interactions is characterized experimentally. The folding rates are faster for designed variants compared with their wild-type proteins, whereas the unfolding rates are largely unaffected. A simple structure-based computational model, which incorporates the Debye-Hückel formalism for the electrostatics, was used and found to qualitatively recapitul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 60 publications
6
64
0
Order By: Relevance
“…Interestingly, we further observed that optimization of the surface charges of TNfn3 significantly reduces the energetic frustration in the MUT TNfn3 compared to the WT. This reduction of energetic frustration upon optimization of charge− charge interactions was previously demonstrated by us using C α -structure-based model 30 and is also in agreement with recent computer simulations of Naganathan et al 31 We also explored the interrelationship between charge− charge interactions and folding mechanism from the correlated fluctuations of the C α atoms at different states for all the three systems of TNfn3. The correlation map captures both the native and non-native interactions from local fluctuations of C α positions of each residue.…”
Section: ■ Discussionsupporting
confidence: 87%
“…Interestingly, we further observed that optimization of the surface charges of TNfn3 significantly reduces the energetic frustration in the MUT TNfn3 compared to the WT. This reduction of energetic frustration upon optimization of charge− charge interactions was previously demonstrated by us using C α -structure-based model 30 and is also in agreement with recent computer simulations of Naganathan et al 31 We also explored the interrelationship between charge− charge interactions and folding mechanism from the correlated fluctuations of the C α atoms at different states for all the three systems of TNfn3. The correlation map captures both the native and non-native interactions from local fluctuations of C α positions of each residue.…”
Section: ■ Discussionsupporting
confidence: 87%
“…S11). Since lower native contact values will likely encounter greater frustration in folding landscapes compared to near native states, and reduced frustration results in increased rates of folding kinetics (72), we anticipate that induced-fit binding occurs more slowly than the binding of open-state conformations.…”
Section: Resultsmentioning
confidence: 99%
“…Using Tanford-Kirkwood electrostatics calculations, they showed reasonable agreement to prediction both for stabilizing and destabilizing mutations on the surface of ubiquitin [44]. Makhatadze further demonstrated this for other proteins like acylphosphatase and Cdc42 with little change in activity [45], and has suggested that the stabilization arises mostly from increased folding rates due to elimination of folding frustration in the native sequences [46]. …”
Section: Surface Electrostaticsmentioning
confidence: 90%